Quantifying self-heating ignition of biochar as a function of feedstock and the pyrolysis reactor temperature. (15th January 2019) - Restuccia, Francesco; Mašek, Ondřej; Hadden, Rory M.; Rein, Guillermo
Abstract: Biochar is produced from biomass through pyrolysis in a reactor under controlled conditions. Different feedstock and reactor temperatures produce materials with different physical and chemical properties. Because biomass, biochar and torrefied biomass are reactive porous media and can undergo self-heating, there is a fire hazard associated to their production, transport, and storage. This hazard needs to be tackled in biomass industries like power generation, where self-heating of biomass can cause significant problems, like the 2012 fire at Tilbury Power Plant (UK). Using basket experiments inside a thermostatically controlled laboratory oven, augmented with thermogravimetry and conductivity measurements, we experimentally study the ignition conditions of pellets and biochar made of softwood, wheat and rice husk. For softwood, we also study biochar produced at different reactor temperatures ranging from 350 to 800 °C. In total, 173 experiments were conducted with 1036 h of oven run time. By investigating the self-heating behaviour of these samples via the Frank-Kamenetskii theory, we quantify and upscale for the first time the reactivity of biochar as a function of feedstock and also of the reactor temperature. The results show that in order from higher to lower tendency to self-heating, the rank is softwood, wheat and rice husk. The reactivity of the softwood is not a monotonic function of pyrolysis reactor temperature but that biochar is most prone to self-heating when produced at 450 °C. Reactivity decreases at higher reactor temperatures, and at 600 °C the biochar is less reactive than the original feedstock. This work improves the fundamental understanding of the fire hazard posed by biomass self-heating, providing insights necessary for successful and safer biomass industries.